Neuropsychological Phenotypes of Pediatric Anti-Myelin Oligodendrocyte Glycoprotein Associated Disorders: A Case Series - Tan, Alexander; Marcus, David J.; Howarth, Robyn A.; Gombolay, Grace Y. (Neuropediatrics, 2021)
Emerging research has demonstrated that anti-myelin oligodendrocyte associated disorders (MOG-AD) are associated with a less severe clinical course than demyelinating conditions associated with the presence of aquaporin-4 antibodies. While a heterogeneity of neuropsychological outcomes in pediatric demyelinating conditions have been described in the literature, no studies to date have investigated the neuropsychological sequelae of pediatric MOG-AD specifically. The objective of the present case series was to describe the clinical and neuropsychological phenotypes of seven pediatric patients (ages 3–15 years) with MOG-AD of different diagnoses (e.g., acute disseminated encephalomyelitis, optic neuritis, multiple sclerosis, and neuromyelitis spectrum disorders). Neuropsychological outcomes were evaluated by retrospective chart review. Results indicated largely intact neuropsychological profiles in five of the seven patients, with mild weaknesses in attention, executive functioning, processing speed, visual-motor/fine-motor skills, and mood concerns being observed. Two patients with a Kurtzke Extended Disability Status Scale of 0 still demonstrated findings on neuropsychological testing. Of the other two patients, one demonstrated higher levels of impairment in the context of a complex medical history and premorbid learning difficulties, while the other demonstrated declines in functioning likely associated with an earlier age of onset. Findings suggest that neuropsychological outcomes may be correspondingly less severe in this population compared with what has previously been described in the pediatric demyelinating disease literature. This differential impact may contribute to the heterogeneity of neuropsychological outcomes found in previous studies, and future research should separate participants with myelin oligodendrocyte antibodies given the difference in clinical course, treatment outcomes, and neuropsychological sequelae.
Keywords: myelin oligodendrocyte glycoprotein; demyelinating diseases; pediatric; neuropsychology